0 votes
283 views
asked by (160 points)

https://socratic.org/questions/if-one-of-the-zeros-of-cubic-polynimial-is-0-the-product-of-then-other-two-zeroe#469288

explain me few steps in the above link in a given solution

how the two zeroes are the zeroes of a quadratic equation

f(x)=ax3+bx2+cx=x(ax2+bx+c)

So the other two zeros are just the zeros of a quadratic in standard form:

please give me a detailed explanation of the steps given in the problem

Request: those who know only answer this.others please leave it blank

1 Answer

+1 vote
answered by (260 points)
If X is one of the zero of the equation then

a*0^3+ b*0^2+c*0+d=0

(X=0)

Gives d=0

So our final equation is

 ax^3+bx^2+cx=0

Take X common and transpose it

X(ax^2+bx+c)=0

ax^2+bx+c=0

Now sum of the roots will be equal to  -b/a

And product of root will be c/a
...